2018
DOI: 10.1186/s41199-018-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

HPV-driven oropharyngeal cancer: current knowledge of molecular biology and mechanisms of carcinogenesis

Abstract: Understanding of oropharyngeal squamous cell carcinoma has significantly progressed over the last decades, and the concept that this disease can be subdivided into two distinct entities based on human papilloma virus (HPV) status has gained acceptance. To combat the constantly growing epidemic of HPV+ oropharyngeal cancer, further investigation and characterization the unique features of the disease, along with the development and implementation of new, targeted therapies, is crucial. In this review, we summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 85 publications
1
97
1
2
Order By: Relevance
“…Standard treatment for OPSCC includes radiation and chemotherapy, which are associated with dose-related morbidities. Patients with papillomavirus-associated oropharyngeal tumors have a better prognosis than those with HPV− OPSCC [21]. HPV+ OPSCC is generally more sensitive to treatment and may respond to de-escalated treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard treatment for OPSCC includes radiation and chemotherapy, which are associated with dose-related morbidities. Patients with papillomavirus-associated oropharyngeal tumors have a better prognosis than those with HPV− OPSCC [21]. HPV+ OPSCC is generally more sensitive to treatment and may respond to de-escalated treatments.…”
Section: Discussionmentioning
confidence: 99%
“…HPV+ OPSCC is generally more sensitive to treatment and may respond to de-escalated treatments. However, treatment for HPV+ and HPV− OPSCC is almost identical [21]. Treatments tailored to the unique etiology of HPV+ disease can be tested using our infection-based model of papillomavirus tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…et al and Lu S. et al study [41,42] showed that Canter immunotherapy could be applied together with chemotherapy for HNSCC patients according to HPV status, and further studies of the new biomarkers-immunological, genetic, or molecular-are needed to be initiated to provide novel targets for improvement of HPV associated HNSCC patient therapy. In addition, markers to identify HPV-positive laryngeal cancer patients with improved prognosis are emerging [43]. These insights are critical to improving our management of this rising disease and exploring effective new treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The infection causes changes in the DNA-repair pathways, mitogenic signaling pathways, cell cycle control, and tumor microenvironment. Molecular heterogeneity within HPV(+) tumors predicts better treatment response [ 8 ]. Biological and treatment responses differ between HPV(+) and HPV(−) patients, which might be associated with heterogeneous epigenetic changes in DNA methylation and the functions of non-coding RNAs, such as miRNAs or lncRNAs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%